2017
DOI: 10.1177/1538574417707900
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Angioscopic Evaluation for Femoropopliteal In-Stent Restenosis Before and After Excimer Laser Atherectomy

Abstract: In-stent restenosis (ISR) is a prevalent problem following stenting of femoropopliteal lesions. A potential novel treatment modality for ISR including excimer laser atherectomy (ELA) has become available. We performed ELA for in-stent chronic total occlusion (CTO) of femoropopliteal lesions and evaluated lesion morphology before and after ELA by angioscopy in 2 patients. The angioscopic findings clearly showed removal of in-stent thrombi after ELA. Thus, ELA may be effective for in-stent CTO of femoropopliteal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…With respect to imaging, intravascular ultrasound assessment indicated that ELA of peripheral artery lesions resulted in significant plaque debulking and increased lumen diameter with negligible degree of adventitial layer injury [11]. Angioscopy assessment also visualized the ELA effect of vaporization of thrombi in femoropopliteal in-stent lesions [12]. Thus, ELA was used as a debulking device.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to imaging, intravascular ultrasound assessment indicated that ELA of peripheral artery lesions resulted in significant plaque debulking and increased lumen diameter with negligible degree of adventitial layer injury [11]. Angioscopy assessment also visualized the ELA effect of vaporization of thrombi in femoropopliteal in-stent lesions [12]. Thus, ELA was used as a debulking device.…”
Section: Discussionmentioning
confidence: 99%
“…9 Drug-coated balloon can reduce smooth muscle cell proliferation to optimize treatment. 10 But vessel calcification may act as a physical barrier to optimal drug penetration and adequate distribution. Meanwhile, the positive remodeling of the artery could be affected by the calcified media.…”
Section: Discussionmentioning
confidence: 99%